Della condizione umana e di altre inquietudini. Infanzia e pratiche di cura in Mozambico - Francesca Cancelliere; Simona Taliani (Archivio Antropologico Mediterraneo)
Based on an ethnography conducted with families of children diagnosed with disabilities, rare diseases, and/or autism spectrum disorders, the article explores the multiple paths taken by mothers in searching for a meaning to attribute to these small and large ailments that push them to the margins of society and family. Within a biomedical system that is often seen as lacking and inadequate, and in the face of local care systems that anchor their interpretations in maternal responsibility, it is the mothers – more than any other member of the nuclear family and lineages – who must struggle against the stigma of a possible guilt. Starting from the vexing nature of non-human (ancestral or spiritual) wills that challenge their moral conduct, the disorder or discomfort of the child is interpreted as the sign, message, or proof of undesirable behaviour carried out by the mothers themselves before or during pregnancy. The article explores some of these stories, beginning with the therapeutic journeys of some patients and their mothers, and suggests viewing this feminine genealogy of childhood diseases as an anthropological challenge to be considered in research-action programmes and training for local social-healthcare personnel.